2013
DOI: 10.1177/1759720x13483187
|View full text |Cite
|
Sign up to set email alerts
|

A review on strontium ranelate long-term antifracture efficacy in the treatment of postmenopausal osteoporosis

Abstract: Osteoporotic fractures are one of the major causes of increased morbidity and mortality in postmenopausal women and the overall aging population. One of the major issues in the management of postmenopausal osteoporosis is to find a safe and effective treatment in the long term (>3 years) to achieve and maintain a reduction in the risk of fracture. Strontium ranelate (PROTELOS ® ) is a relatively novel drug, currently approved in Europe for the treatment of postmenopausal osteoporosis. Strontium ranelate is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
60
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 74 publications
(112 reference statements)
0
60
2
4
Order By: Relevance
“…On one hand, activators of the CaSR have the potential to inhibit PTH secretion and can be used in the treatment of parathyroid hyperfunction; on the other hand, CaSR inhibitors may induce transient PTH increases, which can be anabolic for bone. Strontium ranelate deserves a particular note as a divalent ion that can modulate bone metabolism favoring bone formation and decreasing resorption at least in part through modulation of the CaSR [84].…”
Section: Modulating the Casr For Skeletal Health: Casr Agonists And Amentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, activators of the CaSR have the potential to inhibit PTH secretion and can be used in the treatment of parathyroid hyperfunction; on the other hand, CaSR inhibitors may induce transient PTH increases, which can be anabolic for bone. Strontium ranelate deserves a particular note as a divalent ion that can modulate bone metabolism favoring bone formation and decreasing resorption at least in part through modulation of the CaSR [84].…”
Section: Modulating the Casr For Skeletal Health: Casr Agonists And Amentioning
confidence: 99%
“…It displays a dual mechanism of action, namely, bone forming and anti-resorptive properties, which lead to short-and long-term reduction in vertebral and non-vertebral fractures, such as hip fractures [84,113].…”
Section: Strontium Ranelate: Effects On Bonementioning
confidence: 99%
“…Strontium ranelate is an antiresorptive and bone anabolic agent which has been approved for postmenopausal osteoporosis treatment in Europe (Cianferotti et al, 2013). Preliminary studies showed that strontium ranelate decreases osteoclast differentiation and function simultaneously promoting osteoblastogenesis and osteoblast activity.…”
Section: Strontium Ranelatementioning
confidence: 99%
“…Dieses Ergebnis bestätigten auch die Openlabel-Erweiterungen der Phase-III-Studien Spinal Osteoporosis Therapeutic Intervention (SOTI) und Treatment of Peripheral Osteoporosis (TROPOS), in denen eine kontinuierliche Zunahme der lumbalen Knochendichte über den gesamten Beobachtungszeitraum von 10 Jahren nachgewiesen wurde. Zudem war das relative Risiko für vertebrale Frakturen um 35 % und das für nichtvertebrale Frakturen um 38 % verringert [8].…”
Section: Strontiumranelatunclassified